Determinants of foreign direct investment outflow from India to Poland - Robert Dygas (International Journal of Management and Economics, 2020)
This article concerns the determinants of foreign direct investment (FDI) outflow from India to Poland with some insights to other European countries. This topic strongly relates to globalization of foreign trade and especially new economic initiatives between European Union (EU) and India, which was one of the first countries to develop trade relations with EU. According to CEIC data - Financial Data and Economic Indicators, India's FDI outflow increased slightly to 1.4 billion USD in September 2019 in comparison with 996.5 million USD in September 2018, but it is still below the average of 1.8 billion USD for a period of 2007-2019.1 Very limited number of the scientific research can be found in European literature about India's FDI outflow to EU countries in period of 2004-2019. Indian economists made some research on that topic. Professor J. Ramachandran (listed among the Best Management Thinkers for the year 2015, the first Bain Fellow in India) from Indian Institute of Management Bangalore in 2004 and Professor Jaya Prakesh Pradhan from Central University of Gujarat in 2008 explored the evolution in Indian outward FDI, referring to a shift in the pattern of overseas expansion and basis of competitiveness of Indian companies. The main goal of this article is to explain what really triggers Indian investors to go to Poland and what kind of businesses they form. Some examples of the Indian-based companies are mentioned to support the analysis. The author of this article also researched on different governmental bilateral trade agreements and initiatives, trying to find any direct impacts of that on the India FDI outflow to Poland and other EU countries. He used empirical method of the analysis based on accessible data for period 2004-2019 and literature in that topic and also direct interviews with private Indian investors who made decision to start and run their business in Poland or other EU countries. The main conclusion is that Poland the leader of Visegrad Group is an interesting investment for India and India can be for Poland a counterpart investment partner to China.
Keywords: F21; 650; FDI; vertical FDI; horizontal FDI; India-EU strategic partnership; BTIA; multinational companies; determinants; technology spillovers; FDI Confidence Index